Permafrost and climate change in the Antarctic Peninsula region (PERMANTAR-3) - Vieira, Gonçalo (2014)
There are currently ci 75 GTN-P boreholes and 18 CALM sites in Antarctica, most of them installed during the IPY and still with a short data series. In the Antarctic Peninsula, only 6 boreholes are deeper than 10 m and 4 of them are maintained by the PERMANTAR team. Several new boreholes and CALM sites have been installed in a collaborative effort between Argentina, Brazil, Bulgaria, Portugal, Russia, Spain, Switzerland and the United States. Such an integrated approach, besides contributing to the installation of infrastructure, allowed for new advances on the permafrost thermal state (Vieira et al 2010, Bockheim et al 2013). It is now becoming clear that the Antarctic Peninsula, one of Earth´s regions where air temperature has increased the most in the last 60 years shows a very high sensitivity of permafrost to warming. In the South Shetlands, permafrost temperatures are just below freezing and permafrost degradation is prone to occur. Consequences in the terrestrial ecosystems are still unknown, but changes in hydrology, carbon storage and geomorphological dynamics are expected. The region is a key natural laboratory for understanding permafrost´s reaction to climate change and quite different to the Arctic, with the unique influence on physical and life processes of the Southern Ocean. P3 is taking place from May 2013 to April 2015 and focuses on maintaining and upgrading several GTN-P and CALM sites in the Antarctic Peninsula region, but also on contributing to new questions that developed from on-going work. In this sense, P3 is more than a monitoring project, but an integrated approach aiming at science deliverables dealing with Antarctic permafrost reaction to a changing climate. PERMANTAR´s scope is now enlarged to a latitudinal gradient from 61º to 65ºS in the western Antarctic Peninsula, where we aim at more than traditional focus on permafrost temperature monitoring. Variables linked to permafrost dynamics and modelling are approached in a more integrated way and using state-of-the-art techniques: snow cover dynamics from the local to the regional scale, active layer moisture content, ice-content at the transient layer and changing rates of geomorphic processes. P3 focusses on a set of target questions along the latitudinal gradient: 1) Where is the boundary between continuous and discontinuous permafrost 2) How does the climatic sensitivity of permafrost changes 3) What is the role of late lying snow patches at the continuous permafrost boundary 4) How does soil moisture varies seasonally in the active layer 5) How does ground-ice content occur in the transient layer 6) Can accurate terrain deformation rates be derived by means of DInSAR 7) Can key geomorphic units used as geo-indicators of climate change in the AP.This presentation synthesises the main contributions of the PERMANTAR team with new advances deriving from the Antarctic campaign of 2013-14.